Organizational Justice and its Relationship to Organizational Commitment in Palestinian Universities - Husain Abedalqader; Samir Abuznaid (Randwick International of Social Science Journal, 2022)
The study aimed to identify organizational justice and its relationship to organizational commitment of academics in Palestinian universities. The descriptive analytical approach was used, and a questionnaire was developed for the purpose of the study. The population consisted of all academics (826) at the universities of Hebron and Jerusalem, from which a random sample of 130 employees was taken. The results indicate that academics enjoy their vacations freely, that top administration delegates them some responsibilities, that university administration evaluates academics fairly and equally and assigns them work requirements and tasks that commensurate with their level of scientific expertise, and that academics receive promotions without delay. The administration takes into account the academics’ personal considerations when making career decisions and treats them with respect and dignity when decisions need to be made about their employment. Academics are satisfied with their jobs, and the work climate is appropriate at the universities. Universities provide health insurance for academics and their families, and academics’ loyalty to the university will never waver. Academics participate in departmental decision-making. However, the findings suggest that the role of academic oversight on academic performance at Palestinian universities be activated, including the positive monitoring role of the Palestinian Ministry of Higher Education. Monitoring includes positive oversight of performance and advancement of various university programs to ensure that they address the needs of the Palestinian society. The positive interventions of senior management in universities have a significant impact on motivating and guiding academics. Therefore, the researchers recommend activating and strengthening the positive management role of university administration while staying away from negative interventions. Such intervention would improve academics’ performance, encourage creativity and innovation and enhance knowledge of academics.